CineLibras - A Proposal for Automatic Generation and Distribution of Windows of Libras on the Cinema Rooms - Domingues, Leonardo A.; Ferreira, Felipe L. S.; Araújo, Tiago M. U. de; S. Neto, Manoel; A. Júnior, Lucenildo; Souza Filho, Guido L. de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
Deaf people face many problems to execute their daily activities. The main reasons to explain this include barriers for both access information as well as communicating with people without disabilities. In this context, the main goal of this paper is to identify the main problems faced by deaf people to access information in movie theaters and to propose a solution to better address their requirements. In this context, it was developed a computational system that is able to automatically generate and distribute accessible video tracks in Brazilian Sign Language (Língua Brasileira de Sinais - LIBRAS) in cinema rooms. This solution uses mobile devices as secondary screens, in a way that deaf people can have access to the content presented in their natural way of communication. Finally, experiments were performed with groups of Brazilian deaf in order to ensure the viability of the proposed solution and the data collected are analyzed and discussed.